2004
DOI: 10.1074/jbc.m312353200
|View full text |Cite
|
Sign up to set email alerts
|

DNA Stimulates Mec1-mediated Phosphorylation of Replication Protein A

Abstract: The cellular single-stranded DNA (ssDNA)-binding protein replication protein A (RPA) becomes phosphorylated periodically during the normal cell cycle and also in response to DNA damage. In Saccharomyces cerevisiae, RPA phosphorylation requires the checkpoint protein Mec1, a protein kinase homologous in structure and function to human ATR. We confirm here that immunocomplexes containing a tagged version of Mec1 catalyze phosphorylation of purified RPA, likely reflecting an RPA kinase activity intrinsic to Mec1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 55 publications
4
29
0
Order By: Relevance
“…Next, we determined the role of Dpb11 and DNA in RPA phosphorylation. In agreement with previous studies (9,41), only DNA-bound RPA is an efficient target for phosphorylation by Mec1 (Fig. 1C).…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Next, we determined the role of Dpb11 and DNA in RPA phosphorylation. In agreement with previous studies (9,41), only DNA-bound RPA is an efficient target for phosphorylation by Mec1 (Fig. 1C).…”
Section: Resultssupporting
confidence: 80%
“…In yeast, both the Rpa1 and Rpa2 subunits of RPA are phosphorylated by Mec1 in response to DNA damage (39). In vitro, these two RPA subunits are phosphorylated by Mec1; however, phosphorylation is greatly stimulated when the RPA is bound to ssDNA (40,41). Addition of the 9-1-1 clamp loaded onto DNA stimulates the Mec1-mediated phosphorylation of DNA-bound RPA even further (9).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, functional PP5 was required for the nuclear focus formation and hyperphosphorylation of RPA. Taken together with previous reports that ATR regulates the localization as well as phosphorylation of RPA (6,8), our results suggest an important role of PP5 in the activation of the ATR-mediated checkpoint pathway.…”
Section: Discussionsupporting
confidence: 73%
“…Recent work has shown that RPA bound to ssDNA serves as a binding platform for ATR-and Mec1-containing complexes, thereby localizing these protein kinases to sites of DNA damage (Zou and Elledge 2003). In addition, we have recently shown that ssDNA stimulates RPA phosphorylation catalyzed by immunoprecipitates of Mec1 (Bartrand et al 2004). These results have provided a possible explanation for the induction of RPA phosphorylation in vivo by many different events, all of which involve alterations in DNA structure.…”
Section: H Omologous Recombination During Meiosismentioning
confidence: 99%